Molecular diagnosis of Shigella, Salmonella and Campylobacter by multiplex Real-time PCR in stool culture samples in Ouagadougou (Burkina Faso) - Salfo Sawadogo; Birama Diarra; Cyrille BIsseye; Tegwindé Rebeca Compaore; Florencia W. Djigma; Djénéba Ouermi; Aboubakar S. Ouattara; Jacques Simpore (Sudan Journal of Medical Sciences)
ABSTRACT: